Anti-reflective film

By using a low refractive index layer composed of reactive (meth)acrylate compound with reactive groups and surface-treated alumina particles and hollow silicate particles in the antireflection film, combined with an antifouling layer of fluorine (meth)acrylate compound, the durability of the antifouling film when frequently contacting fingers and solvents is solved, and the antifouling resistance, scratch resistance and wear resistance are improved.

JP7628316B2Pending Publication Date: 2025-02-10HIGASHIYAMA FILM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022198542
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-02-10
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

When the existing anti-reflective films frequently contact fingers and solvents, they have insufficient stain resistance, scratch resistance and wear resistance, and are easily affected by wiping, resulting in a degradation of surface performance.

Method used

A low refractive index layer composed of (meth)acrylate compound containing reactive groups and surface-treated alumina particles and hollow silicate particles is used to combine the anti-fouling layer of fluorine (meth)acrylate compound to form an anti-reflective film to improve the surface water contact angle and solvent resistance.

Benefits of technology

It achieves high stain resistance, scratch resistance and wear resistance, and can withstand the wipes of fingers and solvents, maintaining the stability and durability of surface properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628316000002
    Figure 0007628316000002
  • Figure 0007628316000003
    Figure 0007628316000003
  • Figure 0007628316000004
    Figure 0007628316000004
Patent Text Reader

Abstract

To provide an antireflection film that has excellent excoriation resistance, high antifouling and wear durability, and further has solvent resistance durable against friction by cloth or a hand / finger to which a solvent such as alcohol and the like adhere.SOLUTION: An antireflection film 10 has: a base material film 12; a hard coat layer 14 that is formed on a surface of the base material film 12; and a low refractive index layer 16 that is formed on a surface of the hard coat layer 14. The low refractive index layer 16 is composed of a cured material of an ionization radiation curable composition containing a (meth)acrylate compound having a reactive group, a hollow silica particle, an alumina particle undergoing surface processing by a silane coupling agent having the reactive group allowing bond formation with the (meth)acrylate compound. A water contact angle of a surface of the antireflection film is equal to or more than 100°.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-reflection film, and more particularly to an anti-reflection film suitable for use on the surfaces of displays such as liquid crystal displays, organic EL displays, and touch panels of smartphones and the like. [Background technology]

[0002] An anti-reflective film may be disposed on the display surface of a liquid crystal display, an organic electroluminescence display, a touch panel of a smartphone, etc., in order to prevent reflection of external light on the screen. As an anti-reflective film, one having a hard coat layer and an anti-reflective layer (low refractive index layer) in this order on a substrate film is known. For example, in Patent Document 1 filed by the applicant, the composition of the low refractive index layer formed on the surface of the hard coat layer is examined to improve the anti-reflective property, scratch resistance, and anti-fouling property of the anti-reflective film. In Patent Document 1, a fluorine-containing compound is contained in the low refractive index layer, which contributes to improving the anti-fouling property. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2021 / 020504 Summary of the Invention [Problem to be solved by the invention]

[0004] Anti-reflection films, particularly those placed on the surface of a touch panel, which are frequently touched by fingers, are required to have high anti-soiling properties. As disclosed in Patent Document 1, the anti-soiling properties of the anti-reflection film can be improved by adding a substance having an anti-soiling effect, such as a fluorine-containing compound, to the low refractive index layer constituting the anti-reflection film. On the other hand, a form in which an anti-soiling layer containing the substance having an anti-soiling effect is provided on the surface of the low refractive index layer as a layer independent of the low refractive index layer is also used. However, even if an anti-soiling layer is provided, there are cases in which a sufficiently high anti-soiling property is not obtained, and repeated contact with fingers may cause the surface to wear and the anti-soiling property to decrease. In anti-reflection films which are frequently touched by fingers, in addition to having high anti-reflection properties and anti-soiling properties, from the viewpoint of durability during use, it is important to have high scratch resistance and high wear resistance.

[0005] In recent years, anti-reflection films that are frequently touched by hands and fingers, particularly those placed on the surface of touch panels, are increasingly wiped with a solvent such as alcohol for cleaning and sterilization. However, conventional anti-reflection films have a problem in that the surface of the anti-reflection film is worn away or the antifouling properties are reduced when the film is wiped off with a cloth that has alcohol on it or when the film is repeatedly operated with alcohol-stained fingers.

[0006] The problem to be solved by the present invention is to provide an anti-reflection film that has excellent scratch resistance, as well as high stain resistance and abrasion resistance, and further has solvent resistance sufficient to withstand friction with cloth or fingers contaminated with a solvent such as alcohol. [Means for solving the problem]

[0007] In order to solve the above problems, the anti-reflection film according to the present invention has the following configuration. [1] A first antireflection film according to the present invention is an antireflection film having a base film, a hard coat layer formed on a surface of the base film, and a low refractive index layer formed on the surface of the hard coat layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation-curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and the surface of the antireflection film has a water contact angle of 100° or more.

[0008] [2] In the above aspect [1], the ionizing radiation curable composition constituting the low refractive index layer may further contain a fluorine-containing (meth)acrylate.

[0009] [3] A second antireflection film according to the present invention is an antireflection film having a base film, a hard coat layer formed on a surface of the base film, a low refractive index layer formed on the surface of the hard coat layer, and an antifouling layer formed on the surface of the low refractive index layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation-curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and the antifouling layer is composed of a cured product of an ionizing radiation-curable composition containing a fluorinated (meth)acrylate, and the surface of the antireflection film has a water contact angle of 100° or more.

[0010] [4]See above[3] of In one embodiment, the content of the fluorine-containing (meth)acrylate in the antifouling layer may be 90 mass % or more based on the total solid content of the antifouling layer.

[0011] [5] In the above aspect [3] or [4], the low refractive index layer may not contain a fluorine-containing compound. Effect of the Invention

[0012] The first anti-reflection film according to the present invention having the above-mentioned configuration [1] is an anti-reflection film having a base film, a hard coat layer formed on the surface of the base film, and a low refractive index layer formed on the surface of the hard coat layer, the low refractive index layer being composed of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and the water contact angle of the surface of the anti-reflection film is 100° or more. Since the low refractive index layer is composed of a cured product of a composition containing alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound in addition to the (meth)acrylate compound, the anti-reflection film has excellent scratch resistance, high antifouling properties, and abrasion resistance. Furthermore, since the surface of the anti-reflective film has a water contact angle of 100° or more, the anti-reflective film has high stain resistance and solvent resistance that enables it to withstand friction from cloth or fingers that have solvents such as alcohol on them.

[0013] In the above embodiment [2], the ionizing radiation curable composition constituting the low refractive index layer further contains a fluorine-containing (meth)acrylate, which can effectively enhance the stain resistance and solvent resistance of the surface of the antireflection film.

[0014] The second antireflection film according to the present invention having the above-mentioned configuration [3] is an antireflection film having a base film, a hard coat layer formed on the surface of the base film, a low refractive index layer formed on the surface of the hard coat layer, and an antifouling layer formed on the surface of the low refractive index layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and the antifouling layer is composed of a cured product of an ionizing radiation curable composition containing a fluorine-containing (meth)acrylate, and the water contact angle of the surface of the antireflection film is 100° or more. The low refractive index layer is composed of a cured product of a composition containing alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound in addition to the (meth)acrylate compound, and the low refractive index layer is composed of a cured product of a composition containing alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with .... layer By providing an antifouling layer composed of a cured product of a composition containing a fluorinated (meth)acrylate on the surface of the antireflection film, the antireflection film has excellent scratch resistance, high antifouling properties and abrasion resistance. Furthermore, by providing a water contact angle of 100° or more on the surface of the antireflection film, the antireflection film has high antifouling properties and solvent resistance that can withstand friction with cloth or fingers that have solvents such as alcohol on them.

[0015] In the above embodiment [4], the content of the fluorinated (meth)acrylate in the antifouling layer is 90 mass% or more based on the total solid content of the antifouling layer, thereby effectively enhancing the antifouling properties of the antireflection film.

[0016] In the above embodiment [5], the low refractive index layer does not contain a fluorine-containing compound, so that the scratch resistance of the antireflection film can be effectively improved. [Brief description of the drawings]

[0017] [Figure 1]1 is a cross-sectional view of an antireflection film according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of an antireflection film according to a second embodiment of the present invention. [Diagram 3] FIG. 4 is a cross-sectional view of an antireflection film according to a third embodiment of the present invention. [Figure 4] FIG. 11 is a cross-sectional view of an antireflection film according to a fourth embodiment of the present invention. [Diagram 5] FIG. 11 is a cross-sectional view of an anti-reflection film according to a fifth embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention will be described in detail below. In this specification, various physical properties refer to values ​​at room temperature and in the atmosphere unless otherwise specified. In addition, in this specification, the refractive index of a substance and a substance layer refers to a refractive index at a measurement wavelength of 589.3 nm unless otherwise specified.

[0019] <Anti-reflection film of the first embodiment> Fig. 1 is a cross-sectional view of an antireflection film according to a first embodiment of the present invention. As shown in Fig. 1, an antireflection film 10 according to a first embodiment of the present invention has a substrate film 12, a hard coat layer 14 formed on the surface of the substrate film 12, and a low refractive index layer 16 formed on the surface of the hard coat layer 14. In this embodiment, the above layers are laminated in order without any other layer therebetween. The low refractive index layer 16 is the layer exposed on the outermost surface of the entire antireflection film 10.

[0020] (Base film) The base film 12 is not particularly limited as long as it has transparency. Examples of the base film 12 include a transparent polymer film and a glass film. Transparency means that the total light transmittance in the visible light wavelength region is 50% or more, and the total light transmittance is more preferably 85% or more. The total light transmittance can be measured in accordance with JIS K7361-1 (1997). The thickness of the base film 12 is not particularly limited, but is preferably in the range of 2 μm to 500 μm in terms of excellent handleability, etc. More preferably, it is in the range of 2 μm to 200 μm. Note that, although the term "film" generally refers to a film having a thickness of less than 0.25 mm, if a film having a thickness of 0.25 mm or more can be wound into a roll, the film is also considered to be a film having a thickness of 0.25 mm or more.

[0021] Examples of the polymeric material of the base film 12 include polyester resins such as polyethylene terephthalate resin and polyethylene naphthalate resin, polycarbonate resin, poly(meth)acrylate resin, polystyrene resin, polyamide resin, polyimide resin, polyacrylonitrile resin, polypropylene resin, polyethylene resin, polycycloolefin resin, cycloolefin copolymer resin, and other polyolefin resins, cellulose-based resins such as triacetyl cellulose resin and diacetyl cellulose resin, polyphenylene sulfide resin, polyvinyl chloride resin, polyvinylidene chloride resin, and polyvinyl alcohol resin. The polymeric material of the base film 12 may be composed of only one of these materials, or may be composed of a combination of two or more of these materials. Among these materials, polyethylene terephthalate resin, polyimide resin, polycarbonate resin, poly(meth)acrylate resin, polycycloolefin resin, cycloolefin copolymer resin, and triacetyl cellulose resin are more preferable from the viewpoints of optical properties and durability.

[0022] The base film 12 may be composed of a single layer containing one or more of the above-mentioned polymeric materials, or may be composed of two or more layers, such as a layer containing one or more of the above-mentioned polymeric materials and a layer containing one or more of a different polymeric material.

[0023] (Hard coat layer) The hard coat layer 14 contributes to improving the scratch resistance of the anti-reflection film 10. The hard coat layer 14 is composed of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group. The ionizing radiation means electromagnetic waves or charged particle beams having an energy quantum capable of polymerizing or crosslinking molecules. Examples of the ionizing radiation include ultraviolet rays (UV), X-rays, gamma rays, and other electromagnetic waves, electron beams (EB), alpha rays, ion beams, and other charged particle beams. Among these, ultraviolet rays (UV) are particularly preferred from the viewpoint of productivity. Hereinafter, the ionizing radiation curable composition may be simply referred to as a curable composition. In addition, in this specification, "(meth)acrylate" means "at least one of acrylate and methacrylate". "(meth)acryloyl" means "at least one of acryloyl and methacryloyl". "(meth)acrylic" means "at least one of acrylic and methacrylic". The "(meth)acrylate compound" is a compound having a (meth)acryloyl group, and examples of such compounds include monomers, oligomers, prepolymers, etc. Hereinafter, the (meth)acrylate compound may be simply referred to as (meth)acrylate.

[0024] The (meth)acrylate may be a monofunctional (meth)acrylate or a polyfunctional (meth)acrylate. Alternatively, the (meth)acrylate may be a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. From the viewpoint of improving curability, it is more preferable that the curable composition contains a polyfunctional (meth)acrylate as the (meth)acrylate.

[0025] Examples of (meth)acrylates include urethane (meth)acrylates, silicone (meth)acrylates, alkyl (meth)acrylates, and aryl (meth)acrylates. Among these, urethane (meth)acrylates, particularly urethane (meth)acrylate oligomers, are preferred. Specific examples of urethane (meth)acrylates include those obtained by reacting a polyisocyanate compound with a hydroxyl group-containing (meth)acrylate compound and, if necessary, a polyol compound. Examples of polyisocyanate compounds include diisocyanate compounds such as hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, xylylene diisocyanate, and 4,4'-diphenylmethane diisocyanate, as well as their nurate modified products, adduct modified products, and biuret modified products. Examples of the hydroxyl group-containing (meth)acrylate compound include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, trimethylolpropane diacrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and polyoxyalkylene modified products and polylactone modified products thereof. Examples of the polyol compound include ethylene glycol, P Examples of the curable resin include ethylene glycol, butanediol, hexanediol, polyoxyethylene glycol, polyoxypropylene glycol, glycerin, trimethylolpropane, pentaerythritol, biphenol, and bisphenol. When the curable composition for forming the hard coat layer 14 contains urethane (meth)acrylate as the ultraviolet curable resin, the hard coat layer 14 has a suitable flexibility, so that the antireflection film 10 has high bending resistance and can be suitably used for flexible displays that are repeatedly bent, such as foldable displays and rollable displays. In addition, even if the base film 12 is made of, for example, polycycloolefin or cycloolefin copolymer, which is relatively prone to cracking, cracking of the base film 12 is easily suppressed.

[0026] It is preferable that the (meth)acrylate constituting the curable composition further contains a pentaerythritol (meth)acrylate compound.Specific examples of the pentaerythritol (meth)acrylate compound include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate.In particular, it is preferable that the curable composition contains pentaerythritol tri(meth)acrylate.

[0027] The curable composition forming the hard coat layer 14 may or may not contain a non-UV curable resin in addition to the UV curable resin. The curable composition forming the hard coat layer 14 may also contain a photopolymerization initiator. If necessary, the curable composition may also contain additives that can be generally added to the curable composition. Examples of additives include dispersants, leveling agents, defoamers, thixotropic agents, antifouling agents, antibacterial agents, flame retardants, slip agents, antistatic agents, inorganic particles, and resin particles. If necessary, the curable composition may also contain a solvent.

[0028] Examples of non-UV curable resins include thermoplastic resins, thermosetting resins, etc. Examples of thermoplastic resins include polyester resins, polyether resins, polyolefin resins, polyamide resins, etc. Examples of thermosetting resins include unsaturated polyester resins, epoxy resins, alkyd resins, phenolic resins, etc.

[0029] Examples of the photopolymerization initiator include alkylphenone-based, acylphosphine oxide-based, and oxime ester-based photopolymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2'-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and the like. Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), etc. The photopolymerization initiator may be used alone or in combination of two or more of them.

[0030] The content of the photopolymerization initiator is 0.1% by mass or more and 10% by mass or less based on the total solid content of the curable composition. below It is preferable that the content is in the range of 1% by mass or more and 5% by mass or less.

[0031] The inorganic particles and resin particles can be added to the hard coat layer 14 for the purpose of, for example, preventing blocking of the hard coat layer 14, adjusting the refractive index of the hard coat layer 14, etc. The inorganic particles or resin particles added form fine surface irregularities in the hard coat layer 14, which makes it easier to prevent blocking, which occurs when the hard coat film consisting of the base film 12 and the hard coat layer 14 before the low refractive index layer 16 is formed, is wound into a roll.

[0032] Examples of inorganic particles capable of adjusting the refractive index of the hard coat layer 14 include metal oxide particles made of oxides of metals such as titanium, zirconium, tin, zinc, silicon, niobium, aluminum, chromium, magnesium, germanium, gallium, antimony, and platinum. These may be used alone as inorganic particles capable of adjusting the optical properties, or two or more types may be used in combination. Among these, titanium oxide and zirconium oxide are particularly preferred from the viewpoint of achieving both a high refractive index and excellent transparency. Examples of resin particles include resin particles made of resins such as (meth)acrylic resin, styrene resin, styrene-(meth)acrylic resin, urethane resin, polyamide resin, silicone resin, epoxy resin, phenolic resin, polyethylene resin, and cellulose. These may be used alone as resin particles, or two or more types may be used in combination.

[0033] The thickness of the hard coat layer 14 is not particularly limited, but is preferably 0.5 μm or more from the viewpoint of having sufficient hardness, and more preferably 0.75 μm or more. Also, from the viewpoint of easily suppressing curling due to the difference in thermal shrinkage from the base film 12, it is preferably 20 μm or less, and more preferably 10 μm or less. The thickness of the hard coat layer 14 is the thickness of a relatively smooth portion in the thickness direction that is free of irregularities due to inorganic particles or resin particles.

[0034] From the viewpoint of suppressing interference unevenness caused by the difference in refractive index between the base film 12 and the hard coat layer 14, the refractive index of the hard coat layer 14 is preferably within the range of 1.49 to 1.56. The arithmetic mean roughness Ra of the surface of the hard coat layer 14 on which the surface irregularities are formed is preferably within a range of 0.3 nm or more and 20 nm or less from the viewpoint of suppressing blocking, etc. More preferably, it is 0.5 nm or more and 10 nm or less.

[0035] Examples of the solvent used in the curable composition for forming the hard coat layer 14 include alcohol-based solvents such as ethanol, isopropyl alcohol (IPA), n-butyl alcohol (NBA), ethylene glycol monomethyl ether (EGM), ethylene glycol monoisopropyl ether (IPG), propylene glycol monomethyl ether (PGM), and diethylene glycol monobutyl ether; ketone-based solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, and acetone; aromatic solvents such as toluene and xylene; ester-based solvents such as ethyl acetate (EtAc), propyl acetate, isopropyl acetate, and butyl acetate (BuAc); and amide-based solvents such as N-methylpyrrolidone, acetamide, and dimethylformamide. These may be used alone or in combination of two or more.

[0036] The solids concentration of the curable composition (concentration of components other than the solvent) may be appropriately determined in consideration of coatability, film thickness, etc. For example, it may be 1% by mass or more and 90% by mass or less, 1.5% by mass or more and 80% by mass or less, or 2% by mass or more and 70% by mass or less.

[0037] (Low refractive index layer) In the antireflection film 10 according to this embodiment, a low refractive index layer 16 is provided as an antireflection layer on the surface of the hard coat layer 14. The low refractive index layer 16 has a refractive index lower than that of the hard coat layer 14, and exerts an antireflection effect due to the difference in refractive index between the low refractive index layer 16 and the hard coat layer 14.

[0038] The low refractive index layer 16 is composed of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group as a binder resin, alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and hollow silica particles. As described above for the hard coat layer 14, ionizing radiation includes various electromagnetic waves and charged particle beams, but the low refractive index layer 16 is preferably composed of a cured product of an ultraviolet (UV) curable composition. The reactive groups contained in the (meth)acrylate compound and the silane coupling agent are preferably ultraviolet reactive. A suitable composition of the composition will be described below.

[0039] Examples of the (meth)acrylate compound having a reactive group include urethane (meth)acrylate, silicone (meth)acrylate, alkyl (meth)acrylate, aryl (meth)acrylate, etc. The (meth)acrylate compound may have only a (meth)acryloyl group as the reactive group, or may have another reactive group in addition to the (meth)acryloyl group.

[0040] The (meth)acrylate may be composed of only a monofunctional (meth)acrylate, may be composed of only a polyfunctional (meth)acrylate, or may be composed of a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. It is more preferable that the (meth)acrylate contains a polyfunctional (meth)acrylate.

[0041] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, bornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, di Cyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate, 2-naphthylmethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, (meth)acrylate, 3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate,Examples of the methacrylate include ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.

[0042] Examples of the polyfunctional (meth)acrylate include a bifunctional (meth)acrylate, a trifunctional (meth)acrylate, a tetrafunctional (meth)acrylate, etc. More specifically, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc. pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate.

[0043] The (meth)acrylate compound contained in the curable composition may be composed of one kind of the above-mentioned (meth)acrylate alone or two or more kinds. From the viewpoint of improving scratch resistance, the (meth)acrylate compound contained in the curable composition preferably contains a polyfunctional (meth)acrylate having five or more functional groups, and it is also preferable to increase the content of the polyfunctional (meth)acrylate having five or more functional groups.

[0044] In addition, the polyfunctional (meth)acrylate preferably contains a dimer. The dimer of the polyfunctional (meth)acrylate has an excellent curing speed and can easily increase the curing rate of the curable composition, so that the scratch resistance can be further improved. Among them, it is preferable to contain at least one selected from the group consisting of dimers of pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, and it is more preferable to contain at least one selected from the group consisting of dimers of pentaerythritol triacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.

[0045] From the viewpoints of scratch resistance, transparency, and solubility in a solvent, the content of the dimer is preferably in the range of 25% by mass or more and 50% by mass or less, more preferably 30% by mass or more and 40% by mass or less, based on the total solid content of the polyfunctional (meth)acrylate.

[0046] Furthermore, the curable composition constituting the low refractive index layer 16 preferably contains a fluorine-containing (meth)acrylate as part of the (meth)acrylate compound having a reactive group. This can impart high antifouling properties to the antireflection film 10. Specific examples of fluorine-containing (meth)acrylates include (meth)acrylates containing a perfluoropolyether group. The perfluoropolyether group refers to a polyether such as polyethylene glycol or polypropylene glycol in which all hydrogen atoms have been replaced with fluorine atoms, and examples thereof include perfluoromethyleneoxy. Do(Examples of the repeating units include fluoropolyether groups having a repeating structure of any one of perfluoroethylene oxide (-CF2CF2O-), perfluoropropylene oxide (-CF2CF2CF2O-), perfluoroisopropylene oxide (-CF(CF3)CF2O-), or a combination of a plurality of these. The number of repeating units of the repeating structure is preferably 1 to 100. Specific examples of the compound include "KY-1203", "KY-1207", "KY-1211", "KY-1216", and "KY-1240" manufactured by Shin-Etsu Chemical Co., Ltd., "Megafac RS-75" manufactured by DIC, "Optool DAC-HP" and "Optool DAC-100" manufactured by Daikin Industries, Ltd., and "Ftergent 601AD" and "Ftergent 601ADH2" manufactured by Neos. Such fluorine-containing (meth)acrylates can suppress adhesion of dirt and fingerprints and can facilitate removal of dirt and fingerprints.

[0047] The fluorine-containing (meth)acrylate preferably does not have a urethane bond in its structure. When the fluorine-containing (meth)acrylate does not have a urethane bond in its structure, the hardness of the low refractive index layer 16 is increased, and the low refractive index layer 16 is provided with particularly high abrasion resistance.

[0048] The content of the fluorine-containing (meth)acrylate in the low refractive index layer 16 is preferably 1.0% by mass or more and 15.0% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16. When the content of the fluorine-containing (meth)acrylate in the low refractive index layer 16 is 1.0% by mass or more with respect to 100% by mass of the solid content of the low refractive index layer 16, the slipperiness of the surface of the low refractive index layer 16 is improved, and the scratch resistance is improved. In addition, the stain resistance is improved. From this viewpoint, the content of the fluorine-containing (meth)acrylate in the low refractive index layer 16 is more preferably 3.0% by mass or more, and further preferably 5.0% by mass or more with respect to 100% by mass of the solid content of the low refractive index layer 16. When the content of the fluorine-containing (meth)acrylate in the low refractive index layer 16 is 15.0% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16, the deterioration of the scratch resistance is suppressed. From this viewpoint, the content of the fluorine-containing (meth)acrylate in the low refractive index layer 16 is more preferably 13.0% by mass or less, and even more preferably 10.0% by mass or less, relative to 100% by mass of the solid content of the low refractive index layer 16. The solid content of the low refractive index layer 16 here refers to components other than those that are not fixed to the binder resin in the low refractive index layer 16 and are liquid at room temperature. The solid content of the low refractive index layer 16 includes alumina particles, hollow silica particles, binder resin, etc. It does not include oil components as additives, surfactants that are not fixed to the binder resin, etc.

[0049] The alumina particles, when contained in the low refractive index layer 16, form convex portions on the surface of the low refractive index layer 16. The formation of convex portions on the surface of the low refractive index layer 16 by the alumina particles allows the low refractive index layer 16 to have good scratch resistance.

[0050] The alumina particles may be solid particles or hollow particles, but the alumina particles are preferably solid particles. The solid particles are particles that have substantially no cavities inside the particles, and the ratio of the cavities is less than 5% of the volume of the solid particles. The hollow particles are particles that have cavities inside the particles, and the ratio of the cavities is 5% or more of the volume of the hollow particles. When the alumina particles are solid particles, the scratch resistance of the low refractive index layer 16 is improved, and the scratch resistance of the anti-reflection film 10 is improved. On the other hand, when the alumina particles are hollow particles, the refractive index of the low refractive index layer 16 can be lowered to reduce light reflection. In the hollow particles, the ratio of the cavities is preferably 10% or more and 80% or less of the volume of the hollow particles. When the ratio of the cavities is 10% or more, the refractive index can be lowered to reduce light reflection. It is more preferably 20% or more, and even more preferably 30% or more. On the other hand, when the ratio of the cavities is 80% or less, the decrease in dispersibility of the alumina particles can be suppressed. More preferably, it is 60% or less.

[0051] The shape of the alumina particles is not particularly limited, and may be spherical, needle-like, scaly, rod-like, fibrous, amorphous, etc. Of these, the spherical shape is preferred.

[0052] The alumina particles are surface-treated with a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound. The silane coupling agent has a reactive group capable of forming a bond with a (meth)acrylate compound, so that the alumina particles surface-treated with the silane coupling agent can be firmly bonded to the (meth)acrylate contained in the low refractive index layer 16, and further bonded to the reactive group contained in the adjacent resin layer such as the hard coat layer 14. When these bonds are formed, the abrasion resistance and solvent resistance of the anti-reflection film 10 are improved.

[0053] Silane coupling agents are generally bonded to silicon atoms and have hydrolyzable groups and other functional groups in the molecule. Here, the hydrolyzable group refers to a substituent that is directly bonded to a silicon atom and can generate a siloxane bond by hydrolysis and / or condensation. Examples of the hydrolyzable group include halogen atoms, alkoxy groups, acyloxy groups, and alkenyloxy groups. When the hydrolyzable group has carbon atoms, the number of carbon atoms is preferably 6 or less, and more preferably 4 or less. In particular, an alkoxy group having 4 or less carbon atoms or an alkenyloxy group having 4 or less carbon atoms is preferred. The hydrolyzable group is hydrolyzed to form a bond with an oxygen atom on the surface of the alumina particle, thereby surface-treating the alumina particle.

[0054] The silane coupling agent used here contains a reactive group capable of forming a bond with a (meth)acrylate compound in addition to the hydrolyzable group. Examples of the reactive group include carbon-carbon unsaturated double bond groups such as (meth)acryloyl group, vinyl group, styryl group, and allyl group, and ring-opening polymerizable groups such as epoxy group and oxetanyl group. These reactive groups have ultraviolet light reactivity. In the low refractive index layer 16 containing a (meth)acrylate compound having a reactive group and alumina particles surface-treated with a silane coupling agent having a reactive group, the reactive group of the (meth)acrylate compound reacts with the reactive group of the silane coupling agent to form a bond.

[0055] Examples of silane coupling agents having a carbon-carbon unsaturated double bond group as a reactive group include p-styryltrimethoxysilane, 2-(allyloxymethyl)acrylate (trimethoxysilyl)propyl, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, p-styryltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and 7-octenyltrimethoxysilane.

[0056] Examples of silane coupling agents having a ring-opening polymerizable group as a reactive group include 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 8-glycidoxyoctyltrimethoxysilane.

[0057] Among these, from the viewpoint of reactivity with a (meth)acrylate compound, it is preferable to use a silane coupling agent having a carbon-carbon unsaturated double bond group, and among these, a silane coupling agent having an ethylenic carbon-carbon double bond group such as a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, etc. is particularly preferable.

[0058] The content of the silane coupling agent is preferably in the range of 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the alumina particles. This enhances the effect of the surface treatment by the silane coupling agent. In addition, the scratch resistance of the low refractive index layer 16 can be maintained at a high level, and the wear resistance and solvent resistance can be improved. More preferably, the content is 10 parts by mass or more and 40 parts by mass or less. In the low refractive index layer 16, the silane coupling agent that is not bonded to the alumina particles may remain, and the preferred content range described here refers to the content of the silane coupling agent as a whole, including the silane coupling agent that is not bonded to the alumina particles.

[0059] Alumina particles surface-treated with a silane coupling agent (hereinafter sometimes simply referred to as "alumina particles") form convex portions on the surface of the low refractive index layer 16, and in order to obtain good scratch resistance, the difference (rd) between the average particle diameter r of the alumina particles and the thickness d of the low refractive index layer 16 is preferably 10 nm or more. The difference (rd) is more preferably 15 nm or more, and even more preferably 18 nm or more. On the other hand, from the viewpoint of suppressing the height of the formed convex portions to maintain transparency, the difference (rd) is 300 nm or less. More preferably, it is 200 nm or less, and even more preferably 100 nm or less.

[0060] The average particle diameter r of the alumina particles depends on the thickness d of the low refractive index layer 16, but is preferably in the range of 60 nm to 400 nm. It is more preferably 70 nm or more, and even more preferably 90 nm or more. It is more preferably 300 nm or less, and even more preferably 200 nm or less. The average particle diameter r of the alumina particles is a volume-based average arithmetic value obtained by a laser diffraction / scattering method in accordance with JIS Z8825, and includes not only the primary particle diameter but also the secondary particle diameter which is an aggregate of particles.

[0061] The content of the alumina particles in the low refractive index layer 16 is preferably 0.1% by mass or more and 6.0% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16. When the content of the alumina particles in the low refractive index layer 16 is 0.1% by mass or more with respect to 100% by mass of the solid content of the low refractive index layer 16, excellent scratch resistance can be obtained. From this viewpoint, the content of the alumina particles in the low refractive index layer 16 is more preferably 1.0% by mass or more, and even more preferably 2.0% by mass or more with respect to 100% by mass of the solid content of the low refractive index layer 16. When the content of the alumina particles in the low refractive index layer 16 is 6.0% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16, high transparency can be obtained. From this viewpoint, the content of the alumina particles in the low refractive index layer 16 is more preferably 5.5% by mass or less, and even more preferably 5.0% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16.

[0062] The hollow silica particles are particles having an average particle diameter smaller than the average thickness d of the low refractive index layer 16. The hollow silica particles are preferably particles having an average particle diameter smaller than the alumina particles that form the convex portions on the surface of the low refractive index layer 16. The hollow silica particles are particles that do not substantially contribute to the formation of the surface unevenness of the low refractive index layer 16. The hollow silica particles are particles having cavities inside the particles, and the ratio of the cavities is 5% or more of the volume. The hollow refers to a shell structure consisting of an outer shell and a cavity inside it, or a porous structure having a large number of cavities. The hollow silica particles can reduce the refractive index of the low refractive index layer 16 and reduce the reflection of light by having a hollow structure. The shape of the hollow silica particles is not particularly limited, but is preferably spherical, spindle-shaped, egg-shaped, flat, cubic, amorphous, etc. Among these, spherical, flat, cubic, etc. are particularly preferable.

[0063] In the hollow silica particles, the ratio of the voids is preferably 10% or more and 80% or less by volume. When the ratio of the voids is 10% or more by volume, the refractive index can be lowered to reduce light reflection. More preferably, the ratio is 20% or more by volume, and even more preferably, the ratio is 30% or more by volume. On the other hand, when the ratio of the voids is 80% or less by volume, the decrease in dispersibility of the hollow silica particles can be suppressed. More preferably, the ratio is 60% or less by volume.

[0064] The average particle diameter of the hollow silica particles, depending on the thickness d of the low refractive index layer 16, is preferably 5 nm or more and 100 nm or less. It is more preferably 20 nm or more, and even more preferably 40 nm or more. It is more preferably 80 nm or less, and even more preferably 70 nm or less. When the average particle diameter of the hollow silica particles is within these preferred ranges, excellent anti-reflection effect and transparency can be obtained in the low refractive index layer 16. The average particle diameter is a volume-based average arithmetic value obtained by a laser diffraction / scattering method according to JIS Z8825. It includes not only the primary particle diameter but also the secondary particle diameter which is an aggregate of particles.

[0065] The refractive index of the hollow silica particles is preferably in the range of 1.01 to 1.45, more preferably in the range of 1.15 to 1.38, and even more preferably in the range of 1.15 to 1.35. When the refractive index of the hollow silica particles is in this range, excellent antireflection effect can be obtained.

[0066] The content of the hollow silica particles in the low refractive index layer 16 is preferably 6.0% by mass or more and 49.9% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16. End In this case, excellent antireflection properties can be obtained. From this viewpoint, the content of hollow silica particles in the low refractive index layer 16 is more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more, based on 100% by mass of the solid content of the low refractive index layer 16. If the content of hollow silica particles in the low refractive index layer 16 is 49.9% by mass or less, based on 100% by mass of the solid content of the low refractive index layer 16, the deterioration of scratch resistance is suppressed. From this viewpoint, the content of hollow silica particles in the low refractive index layer 16 is more preferably 45% by mass or less, further preferably 40% by mass or less, based on 100% by mass of the solid content of the low refractive index layer 16.

[0067] The total amount of the alumina particles and hollow silica particles in the low refractive index layer 16 is preferably 10% by mass or more and 50% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16. When the total amount of the alumina particles and hollow silica particles in the low refractive index layer 16 is 10% by mass or more with respect to 100% by mass of the solid content of the low refractive index layer 16, excellent scratch resistance can be obtained. From this viewpoint, the total amount of the alumina particles and hollow silica particles in the low refractive index layer 16 is more preferably 20% by mass or more, and even more preferably 30% by mass or more with respect to 100% by mass of the solid content of the low refractive index layer 16. On the other hand, when the total amount of the alumina particles and hollow silica particles in the low refractive index layer 16 is 50% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16, the alumina particles and hollow silica particles can be sufficiently held in the low refractive index layer 16, and therefore excellent scratch resistance can be obtained. From this viewpoint, the total amount of alumina particles and hollow silica particles in the low refractive index layer 16 is more preferably 45 mass % or less, and further preferably 40 mass % or less, relative to 100 mass % of the solid content of the low refractive index layer 16.

[0068] The low refractive index layer 16 is formed using an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and hollow silica particles. In the low refractive index layer 16, through irradiation with ionizing radiation, bonds are formed between the (meth)acrylic compounds, between the surface-treated alumina particles, between the (meth)acrylic compounds and the surface-treated alumina particles, and between the (meth)acrylic compounds or the surface-treated alumina particles and components having reactive groups contained in adjacent layers, thereby making the low refractive index layer 16 have high scratch resistance, wear resistance, and solvent resistance. As described above, the reactive groups contained in the (meth)acrylic compounds and the silane coupling agent are preferably ultraviolet-reactive. When the (meth)acrylic compound and the alumina particles have ultraviolet-reactive reactive groups, by irradiating ultraviolet light on the low refractive index layer 16 formed from a composition containing the (meth)acrylic compound and the surface-treated alumina particles, the scratch resistance, abrasion resistance, and solvent resistance of the low refractive index layer 16 are improved, and the scratch resistance, abrasion resistance, and solvent resistance of the antireflection film 10 are improved.

[0069] In addition, the composition for forming the low refractive index layer 16 preferably contains a photopolymerization initiator when the (meth)acrylic compound contains one having a reactive group reactive to ultraviolet light (when the composition is an ultraviolet curable resin). Furthermore, the composition for forming the low refractive index layer 16 may contain a solvent (a solvent used as a dispersion medium in a particle dispersion of alumina particles, and / or a solvent added separately thereto) as necessary. The binder resin of the low refractive index layer 16 may be composed of only an ultraviolet curable resin such as a (meth)acrylic resin, or may be composed of a combination of an ultraviolet curable resin and a non-ultraviolet curable resin. As the non-ultraviolet curable resin, photopolymerization initiator, and solvent, the chemical species listed above as specific examples of those that can be contained in the composition for forming the hard coat layer 14 can also be suitably applied to the composition for forming the low refractive index layer 16.

[0070] The content of the photopolymerization initiator is preferably in the range of 0.1% by mass or more and 10% by mass or less, based on the total solid content of the composition for forming the low refractive index layer 16. More preferably, it is 1% by mass or more and 5% by mass or less.

[0071] In addition, the low refractive index layer 16 may contain additives, etc., as necessary. Examples of such additives include dispersants, leveling agents, defoamers, thixotropic agents, antibacterial agents, flame retardants, slip agents, refractive index adjusters, inorganic particles other than alumina particles, and resin particles. When inorganic particles other than alumina particles are contained, the inorganic particles may also be surface-treated with a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound, like the alumina particles.

[0072] In this embodiment, the water contact angle of the surface of the antireflection film 10, that is, the surface of the low refractive index layer 16, is 100° or more. This allows the antireflection film 10 to have high antifouling properties. In addition, the slipperiness of the surface of the low refractive index layer 16 is improved, which contributes to improving scratch resistance. From the viewpoint of obtaining higher antifouling properties, the water contact angle of the surface of the low refractive index layer 16 is preferably 105° or more, more preferably 110° or more. The water contact angle of the surface of the low refractive index layer 16 depends on the component composition of the constituent material of the low refractive index layer 16. For example, the water contact angle is increased by including a fluorine-containing (meth)acrylate or a silicone-containing (meth)acrylate in the low refractive index layer 16. In addition, the water contact angle of the surface of the low refractive index layer 16 can be increased by providing fine irregularities to the surface of the low refractive index layer 16, and in this embodiment, the alumina particles contained in the low refractive index layer 16 can play that role. However, imparting unevenness to the surface of the low refractive index layer 16 may reduce the wipeability of the surface, and from the viewpoint of reducing this possibility, it is preferable to increase the water contact angle by using a method of adding a fluorine-containing (meth)acrylate or a silicone-containing (meth)acrylate instead of or in addition to the method of imparting unevenness. There is no particular upper limit to the water contact angle of the surface of the low refractive index layer 16, but it is generally 130° or less.

[0073] The refractive index of the low refractive index layer 16 is not particularly limited as long as it is lower than that of the hard coat layer 14, but is preferably 1.35 or more and 1.52 or less. When the refractive index is 1.35 or more, the strength of the low refractive index layer 16 can be made sufficient, and good scratch resistance can be obtained. On the other hand, when the refractive index is 1.52 or less, the reflectance of the antireflection film 10 can be further reduced. From the above viewpoints, the refractive index of the low refractive index layer 16 is more preferably 1.38 or more and 1.50 or less, and even more preferably 1.40 or more and 1.49 or less.

[0074] The average thickness d of the low refractive index layer 16 is preferably in the range of 80 nm to 110 nm. More preferably, it is 85 nm or more, and even more preferably, it is 90 nm or more. Also, it is more preferably 105 nm or less, and even more preferably, it is 100 nm or less. Within this range, a good low luminous reflectance can be obtained, and light reflection can be reduced. The thickness of the low refractive index layer 16 is the thickness of a relatively smooth portion in a portion without unevenness caused by alumina particles in the thickness direction.

[0075] (Anti-reflection film manufacturing method) To manufacture the anti-reflection film 10, the hard coat layer 14 and the low refractive index layer 16 may be formed in this order. To form each layer, a composition for forming each layer may be applied, dried as necessary, and then cured by a method according to the curing property of the composition, such as irradiation with ionizing radiation including ultraviolet rays. After forming a layer, a composition for forming the next layer may be applied, dried as necessary, and then cured. By sequentially repeating this process, a laminated structure of the hard coat layer 14 and the low refractive index layer 16 may be formed, and the anti-reflection film 10 may be manufactured.

[0076] A wet method can be suitably used for coating the composition forming each layer. Specifically, for example, various coating methods such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, kiss coating, etc., and various printing methods such as inkjet printing, offset printing, screen printing, flexographic printing, etc. can be used.

[0077] The drying step for each layer is not particularly limited as long as it can remove the solvent used in the coating liquid, but is preferably performed at a temperature of 50 to 150° C. for about 10 to 180 seconds.

[0078] For the irradiation of each layer with ultraviolet light, a high-pressure mercury lamp, an electrodeless (microwave type) lamp, a xenon lamp, a metal halide lamp, or any other ultraviolet light irradiation device can be used. The ultraviolet light irradiation may be performed in an inert gas atmosphere such as nitrogen, if necessary. The amount of ultraviolet light irradiation is not particularly limited, but is preferably 50 to 800 mJ / cm. 2 is preferable, and 100 to 300 mJ / cm 2 is more preferred.

[0079] When forming the hard coat layer 14 on the surface of the base film 12, the surface of the base film 12 may be subjected to a surface treatment before coating in order to improve adhesion between the base film 12 and the hard coat layer 14. Examples of the surface treatment include corona treatment, plasma treatment, hot air treatment, ozone treatment, and ultraviolet treatment.

[0080] (Characteristics of anti-reflective film) The antireflection film 10 having the above configuration has a base film 12, a hard coat layer 14 formed on the surface of the base film 12, and a low refractive index layer 16 formed on the surface of the hard coat layer 14. The low refractive index layer 16 is composed of a cured product of an ionizing radiation-curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles that have been surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound. The water contact angle of the surface of the antireflection film 10 is 100° or more, and as a result, the film has excellent scratch resistance, as well as high antifouling properties, abrasion resistance, and solvent resistance.

[0081] In the anti-reflection film 10 according to this embodiment, the water contact angle of the surface is 100° or more, so that the anti-reflection film 10 has high anti-soiling properties. Since the anti-reflection film 10 has high anti-soiling properties, stains such as fingerprints are less likely to adhere to the surface of the anti-reflection film 10, and even if they do adhere, they can be easily removed. In addition, in the anti-reflection film 10 according to this embodiment, the alumina particles contained in the low refractive index layer 16 contribute to the scratch resistance of the anti-reflection film 10. Furthermore, the alumina particles are surface-treated as described above, and bonds are formed between the alumina particles and the (meth)acrylate compound, which contributes to improving the abrasion resistance and solvent resistance. Thus, the anti-reflection film 10 according to this embodiment has high anti-reflection properties and anti-soiling properties as well as high scratch resistance, abrasion resistance, and solvent resistance, and is therefore particularly suitable for applications that are frequently touched by fingers, including those placed on the surface of a touch panel. Because the anti-reflection film 10 has high solvent resistance, the surface can maintain a high scratch resistance and abrasion resistance even when the surface of the anti-reflection film 10 is rubbed with a cloth or fingers that have a solvent such as alcohol on it for cleaning, sterilization, etc.

[0082] From the viewpoint of good visibility, the haze of the antireflection film 10 is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.0 or less. The luminous reflectance of the antireflection film 10 is preferably as low as possible, more preferably 2.5% or less, and even more preferably 2.0% or less. If the luminous reflectance is 2.0% or less, the antireflection film 10 can be considered to have sufficiently high antireflection properties.

[0083] From the viewpoint of achieving both scratch resistance and abrasion resistance, the arithmetic mean roughness Ra of the surface of the low refractive index layer 16 is preferably within a range of 1.0 nm to 20 nm, more preferably 3.0 nm to 15 nm, and further preferably 5.0 nm or more and 10 nm or less.

[0084] <Anti-reflection film of second embodiment> 2 shows an antireflection film 20 according to the second embodiment. The antireflection film 20 according to the second embodiment has a base film 12, a hard coat layer 14 formed on the surface of the base film 12, a low refractive index layer 16 formed on the surface of the hard coat layer 14, and an antifouling layer 18 formed on the surface of the low refractive index layer 16.

[0085] The antireflection film 20 according to the second embodiment differs from the antireflection film 10 according to the first embodiment in that it has an antifouling layer 18 on the surface of the low refractive index layer 16. Other than this, it is similar to the antireflection film 10 according to the first embodiment, and therefore a description of the similar configuration will be omitted.

[0086] (Anti-stain layer) In the antireflection film 20 according to this embodiment, an antifouling layer 18 is provided on the surface of the low refractive index layer 16. The antifouling layer 18 enhances the antifouling properties of the antireflection film 20.

[0087] The stain-resistant layer 18 is made of a cured product of an ionizing radiation curable composition containing a fluorine-containing (meth)acrylate, and is particularly preferably made of a cured product of an ultraviolet ray curable composition.

[0088] Since the antifouling layer 18 is composed of a cured product of a composition containing a fluorine-containing (meth)acrylate, the antireflection film 20 having the antifouling layer 18 on its surface has excellent antifouling properties, solvent resistance, abrasion resistance, and scratch resistance. Specific examples of fluorine-containing (meth)acrylates include (meth)acrylates containing a perfluoropolyether group. A perfluoropolyether group refers to a polyether such as polyethylene glycol or polypropylene glycol in which all hydrogen atoms have been replaced with fluorine atoms, and examples thereof include perfluoromethyleneoxy Do( Examples of the repeating unit include fluoropolyether groups having a repeating structure of any one of perfluoroethylene oxide (-CF2CF2O-), perfluoropropylene oxide (-CF2CF2CF2O-), perfluoroisopropylene oxide (-CF(CF3)CF2O-), or a combination of a plurality of these. The number of repeating units of the repeating structure is preferably 1 to 100. Specific examples of the compound include "KY-1203", "KY-1207", "KY-1211", "KY-1216", and "KY-1240" manufactured by Shin-Etsu Chemical Co., Ltd., "Megafac RS-75" manufactured by DIC, "Optool DAC-HP" and "Optool DAC-100" manufactured by Daikin Industries, and "Ftergent 601AD" and "Ftergent 601ADH2" manufactured by Neos.

[0089] The fluorine-containing (meth)acrylate preferably does not have a urethane bond in its structure. When the fluorine-containing (meth)acrylate does not have a urethane bond in its structure, the hardness of the antifouling layer 18 is increased, and the antifouling layer 18 is provided with particularly high abrasion resistance.

[0090] In the antifouling layer 18, the content of the fluorine-containing (meth)acrylate is preferably 90% by mass or more based on the total solid content of the antifouling layer 18. This makes it possible to obtain a high antifouling effect due to the fluorine-containing (meth)acrylate. From the viewpoint of further enhancing the effect of improving the antifouling property, the content of the fluorine-containing (meth)acrylate in the antifouling layer 18 is more preferably 92% by mass or more based on the total solid content of the antifouling layer 18. Moreover, it is more preferable that the total amount of the resin components constituting the antifouling layer 18, excluding unavoidable components, is the fluorine-containing (meth)acrylate. The solid content of the antifouling layer 18 here refers to components in the antifouling layer 18 that are not fixed by the curable component and are liquid at room temperature. The solid content of the antifouling layer 18 includes fluorine-containing (meth)acrylate and the like.

[0091] The antifouling layer 18 can be formed using a composition containing a fluorine-containing (meth)acrylate. The composition for forming the antifouling layer 18 may be arranged in the form of a layer on the surface of the low refractive index layer 16 and then cured. When the antifouling layer 18 is formed as a cured product of a composition having ultraviolet curing properties, it is preferable that the composition for forming the antifouling layer 18 further contains a photopolymerization initiator. In addition, it may contain a solvent as necessary.

[0092] As the photopolymerization initiator and the solvent, the chemical species given above as specific examples of those that can be contained in the composition for forming the hard coat layer 14 can also be suitably applied to the composition for forming the antifouling layer 18. The content of the photopolymerization initiator is preferably in the range of 0.1% by mass or more and 15% by mass or less, based on the total solid content of the composition for forming the antifouling layer 18. It is more preferably 3% by mass or more and 10% by mass or less.

[0093] In addition, the antifouling layer 18 may contain additives, etc., as necessary. Examples of such additives include antifouling agents other than fluorine-containing (meth)acrylates, dispersants, leveling agents, defoamers, thixotropic agents, antibacterial agents, flame retardants, slip agents, and refractive index adjusters. However, from the viewpoint of increasing the surface smoothness of the antifouling layer 18, the antifouling layer 18 may contain metal oxide particles such as alumina particles. transformation It is preferable that the antifouling layer 18 does not contain solid particles, including solid particles and hollow silica particles. Even if the antifouling layer 18 contains solid particles, it is preferable that the particle size of the solid particles is kept to 10 nm or less, and the content of the solid particles is kept to 1 mass % or less relative to 100 mass % of the solid content of the antifouling layer 18.

[0094] In this embodiment, the water contact angle of the surface of the antireflection film 20, that is, the surface of the antifouling layer 18, is 100° or more. This provides the antireflection film 20 with high antifouling properties. In addition, the slipperiness of the surface of the antifouling layer 18 is improved, which contributes to improving scratch resistance. From the viewpoint of obtaining higher antifouling properties, the water contact angle of the surface of the antifouling layer 18 is preferably 105° or more, more preferably 110° or more. The water contact angle of the surface of the antifouling layer 18 is increased, for example, by increasing the content of fluorine-containing (meth)acrylate in the antifouling layer 18. There is no particular upper limit to the water contact angle of the surface of the antifouling layer 18, but it is generally 130° or less.

[0095] The thickness of the antifouling layer 18 is preferably 1 nm or more. This allows the antifouling layer 18 to have a high effect of improving the antifouling properties. More preferably, the thickness of the antifouling layer 18 is 3 nm or more, and even more preferably 5 nm or more. On the other hand, the thickness of the antifouling layer 18 is preferably 15 nm or less. This allows the antireflection properties of the antireflection film 20 to be maintained at a high level. More preferably, the thickness of the antifouling layer 18 is 10 nm or less.

[0096] The refractive index of the antifouling layer 18 is preferably 1.6 or less. If it is 1.6 or less, the antireflection property of the antireflection film 20 can be maintained high. More preferably, the refractive index of the antifouling layer 18 is 1.55 or less, and further preferably 1.50 or less. On the other hand, the refractive index of the antifouling layer 18 is not particularly limited as long as the thickness of the antifouling layer 18 is within the above range, but is preferably 1.3 or more, and more preferably 1.35 or more.

[0097] From the viewpoint of achieving both scratch resistance and abrasion resistance, the arithmetic mean roughness Ra of the surface of the antifouling layer 18 is preferably within a range of 1.0 nm to 20 nm, more preferably 3.0 nm to 15 nm, and even more preferably 5.0 nm or more and 10 nm or less.

[0098] In the antireflection film 20 according to this embodiment, the composition of the low refractive index layer 16 may be the same as that in the antireflection film 10 according to the first embodiment. However, unlike the antireflection film 10 according to the first embodiment, the antifouling layer 18 is provided on the low refractive index layer 16, and the antifouling layer 18 exhibits high antifouling properties, so that the low refractive index layer 16 does not need to contain a fluorine-containing compound for the purpose of improving the antifouling properties. If a large amount of a fluorine-containing compound is contained in the low refractive index layer 16, the wettability with the composition for forming the antifouling layer 18 decreases, and the adhesion with the antifouling layer 18 weakens, leading to a decrease in the scratch resistance of the antireflection film 20. However, by making the low refractive index layer 16 free of a fluorine-containing compound, the scratch resistance of the antireflection film 20 can be improved. Even if a fluorine-containing compound is contained in the low refractive index layer 16, the content of the fluorine-containing compound is preferably kept to 1% by mass or less with respect to 100% by mass of the solid content of the low refractive index layer 16.

[0099] In the antireflection film 20 according to this embodiment, an antifouling layer 18 is provided in direct contact with the surface of the low refractive index layer 16. For example, a primer layer having an adhesion improving effect, such as a layer made of a non-fluorine-containing (meth)acrylate resin, is not formed on the surface of the low refractive index layer 16. By not providing such a primer layer, the structure of the antireflection film 20 can be simplified, and the productivity and cost reduction effect of the antireflection film 20 can be improved.

[0100] <Other types of anti-reflective film> As described above, the antireflection film according to the present invention is a film in which the hard coat layer 14 and the low refractive index layer 16 are laminated in this order on the surface of the base film 12, and an antifouling layer 18 is further laminated on the surface, and the antireflection film is not limited to the configuration of the antireflection film 10 according to the first embodiment or the antireflection film 20 according to the second embodiment as long as the low refractive index layer 16 has a predetermined composition. Other embodiments of the antireflection film according to the present invention will be exemplified below.

[0101] Third embodiment 3 shows an antireflection film 30 according to a third embodiment. The antireflection film 30 according to the third embodiment has a base film 12, a hard coat layer 14 formed on the surface of the base film 12, a high refractive index layer 15 formed on the surface of the hard coat layer 14, and a low refractive index layer 16 formed on the surface of the high refractive index layer 15.

[0102] The antireflection film 30 according to the third embodiment differs from the antireflection film 10 according to the first embodiment in that a high refractive index layer 15 is provided between the hard coat layer 14 and the low refractive index layer 16. Other than this, it is similar to the antireflection film 10 according to the first embodiment, and therefore a description of the similar configuration will be omitted.

[0103] The high refractive index layer 15 is a layer having a higher refractive index than the hard coat layer 14 and the low refractive index layer 16. By providing the high refractive index layer 15 between the hard coat layer 14 and the low refractive index layer 16, the antireflection film 30 exhibits a higher antireflection effect. The refractive index of the high refractive index layer 15 is preferably in the range of 1.55 or more and 1.80 or less, and more preferably 1.60 or more and 1.70 or less.

[0104] The material of the high refractive index layer 15 is not particularly limited, and may be any known material conventionally used in anti-reflection films, etc., so as to obtain a desired refractive index. For example, the material may be appropriately selected from the materials described above as usable in the hard coat layer 14 and the low refractive index layer 16. The refractive index of the high refractive index layer 15 can be adjusted by the type and amount of binder resin, inorganic oxide particles, and resin particles. For example, by adding a sufficient amount of inorganic oxide particles, a high refractive index layer 15 having a higher refractive index than the low refractive index layer 16 can be formed.

[0105] The average thickness of the high refractive index layer 15 varies depending on the refractive index setting, but by setting it to, for example, 50 nm or more and 200 nm or less, the antireflection function can be further improved. The high refractive index layer 15 may be provided by laminating two or more layers having mutually different refractive indices.

[0106] Fourth embodiment FIG. 4 shows an anti-reflection film 40 according to a fourth embodiment. The anti-reflection film 40 according to the fourth embodiment has a base film 12, a hard coat layer 14 formed on one surface of the base film 12, and a low refractive index layer 16 formed on the surface of the hard coat layer 14. The base film 12 also has a transparent adhesive layer 22 on the other surface. A release film 24 is disposed on the surface of the transparent adhesive layer 22 as necessary. The release film 24 functions as a protective layer for the transparent adhesive layer 22 before use of the anti-reflection film 40, and is peeled off from the transparent adhesive layer 22 when the anti-reflection film 40 is used.

[0107] The anti-reflection film 40 of the fourth embodiment differs from the anti-reflection film 10 of the first embodiment in that it has a transparent adhesive layer 22 on the other side of the base film 12, but is otherwise similar to the anti-reflection film 10 of the first embodiment, and therefore a description of the similar configuration will be omitted.

[0108] The transparent adhesive layer 22 is for attaching the anti-reflection film 40 to the surface of a display or the like with good adhesion. In addition, the anti-reflection film 40 has the effect of preventing glass of a display or the like from shattering by having the transparent adhesive layer 22. That is, the anti-reflection film 40 also functions as a shatterproof film.

[0109] The adhesive composition forming the transparent adhesive layer 22 may contain a known adhesive resin such as an acrylic adhesive, a silicone adhesive, or a urethane adhesive. Among them, an acrylic adhesive is preferred from the viewpoint of optical transparency and heat resistance. The adhesive composition preferably contains a crosslinking agent to increase the cohesive force of the transparent adhesive layer 22. Examples of the crosslinking agent include an isocyanate crosslinking agent, an epoxy crosslinking agent, an aziridine crosslinking agent, and a chelate crosslinking agent.

[0110] The pressure-sensitive adhesive composition may contain additives as necessary. Examples of additives include known additives such as plasticizers, silane coupling agents, surfactants, antioxidants, fillers, curing accelerators, and curing retarders. In addition, from the viewpoint of productivity, the pressure-sensitive adhesive composition may be diluted with an organic solvent.

[0111] The thickness of the transparent adhesive layer 22 is not particularly limited, but is preferably within the range of 5 μm to 100 μm, more preferably 10 μm or more and 50 μm or less.

[0112] The transparent adhesive layer 22 can be formed by a method of directly applying an adhesive composition onto the other side of the base film 12, a method of applying an adhesive composition onto the side of a release film 24 and then transferring it onto the other side of the base film 12, or a method of applying an adhesive composition onto the side of a first release film and then laminating a second release film, peeling off one of the release films, and transferring it onto the other side of the base film 12.

[0113] From the viewpoint of the effect of preventing glass from scattering, the transparent adhesive layer 22 preferably has an adhesive strength to glass of 4 N / 25 mm or more, more preferably 6 N / 25 mm or more, and further preferably 10 N / 25 mm or more.

[0114] Fifth embodiment 5 shows an anti-reflection film 50 according to a fifth embodiment. The anti-reflection film 50 according to the fifth embodiment has a base film 12, a hard coat layer 14 formed on one surface of the base film 12, a low refractive index layer 16 formed on the surface of the hard coat layer 14, and a protective film 28 arranged on the surface of the low refractive index layer 16 via an adhesive layer 26. In addition, a transparent adhesive layer 22 is formed on the other surface of the base film 12. A release film 24 is arranged on the surface of the transparent adhesive layer 22 as necessary.

[0115] The anti-reflection film 50 of the fifth embodiment differs from the anti-reflection film 40 of the fourth embodiment in that it has a protective film 28 on the surface of the low refractive index layer 16 via an adhesive layer 26, but is otherwise similar to the anti-reflection film 40 of the fourth embodiment, and therefore a description of the similar configuration will be omitted.

[0116] The protective film 28 can prevent the surface of the low refractive index layer 16 from being scratched when the antireflection film 50 is handled, for example, by continuous processing in a roll process or by bonding to a display or the like. The protective film 28 is attached to the surface of the low refractive index layer 16 via the adhesive layer 26. The protective film 28 is peeled off from the surface of the low refractive index layer 16 together with the adhesive layer 26 after processing of the antireflection film 50. For this reason, the adhesive layer 26 is adjusted to have a stronger adhesive force between the protective film 28 and the adhesive layer 26 than between the low refractive index layer 16 and the adhesive layer 26, so that the adhesive force between the low refractive index layer 16 and the adhesive layer 26 can be peeled off at the interface. In the antireflection film 50 according to this embodiment, the water contact angle of the surface is specified with respect to the surface in a state in which the protective film 28 and the adhesive layer 26 are peeled off, and the water contact angle on the surface after they are peeled off is 100° or more.

[0117] The material constituting the protective film 28 can be appropriately selected from those exemplified as the material constituting the base film 12. The thickness of the protective film 28 is not particularly limited, but can be in the range of 2 μm or more and 500 μm or less, or in the range of 2 μm or more and 200 μm or less.

[0118] The adhesive layer 26 may suitably be one described in Patent Document 1. The adhesive forming the adhesive layer 26 is not particularly limited, and an acrylic adhesive, a silicone adhesive, a urethane adhesive, or the like may suitably be used. In particular, an acrylic adhesive is suitable because of its excellent transparency and heat resistance. The acrylic adhesive is preferably formed from an adhesive composition containing a (meth)acrylic polymer and a crosslinking agent.

[0119] The (meth)acrylic polymer is a homopolymer or copolymer of a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include an alkyl group-containing (meth)acrylic monomer, a carboxyl group-containing (meth)acrylic monomer, and a hydroxyl group-containing (meth)acrylic monomer.

[0120] Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, a metal chelate-based crosslinking agent, a metal alkoxide-based crosslinking agent, a carbodiimide-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a melamine-based crosslinking agent, etc. The crosslinking agent may be used alone or in combination of two or more.

[0121] The adhesive composition may contain other additives in addition to the (meth)acrylic polymer and the crosslinking agent. Examples of other additives include crosslinking accelerators, crosslinking retarders, tackifiers, antistatic agents, silane coupling agents, plasticizers, peeling aids, pigments, dyes, wetting agents, thickeners, UV absorbers, preservatives, antioxidants, metal deactivators, alkylating agents, and flame retardants. These are appropriately selected and used depending on the application and purpose of the adhesive.

[0122] The thickness of the adhesive layer 26 is not particularly limited, but is preferably within the range of 1 μm or more and 10 μm or less, and more preferably 2 μm or more and 7 μm or less.

[0123] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0124] For example, in the above embodiment, it is described that the surface of the base film 12 may be subjected to a surface treatment. However, instead of the surface treatment, an easy-adhesion layer may be provided on the surface of the base film 12 .

[0125] The high refractive index layer 15 in the third embodiment is shown in FIG. 3 as being added to the anti-reflection film 10 of the first embodiment shown in FIG. 1, but may be added to the anti-reflection film 20 of the second embodiment shown in FIG. 2. The transparent adhesive layer 22 and the release film 24 in the fourth embodiment are shown in FIG. 4 as being added to the anti-reflection film 10 of the first embodiment shown in FIG. 1, but may be added to the anti-reflection film 20 of the second embodiment shown in FIG. 2 or the anti-reflection film 30 of the third embodiment shown in FIG. 3. The adhesive layer 26 and the protective film 28 in the fifth embodiment are shown in FIG. 5 as being added to the anti-reflection film 40 of the fourth embodiment shown in FIG. 4, but may be added to the anti-reflection film 10 of the first embodiment shown in FIG. 1 or the anti-reflection film 20 of the second embodiment shown in FIG. 2, or may be added to the anti-reflection film 30 of the third embodiment shown in FIG. 3. When an adhesive layer 26 and a protective film 28 are added to the anti-reflection film 20 of the second embodiment, the adhesive layer 26 is adjusted so that the adhesive strength between the protective film 28 and the adhesive layer 26 is stronger than the adhesive strength between the anti-fouling layer 18 and the adhesive layer 26, and so that interfacial peeling is possible between the anti-fouling layer 18 and the adhesive layer 26.

[0126] Prior to forming each layer, various functional layers such as a gas barrier improving layer, an antistatic layer, and an oligomer block layer may be provided on the surface of the base film 12. As the antistatic layer, the one described in Patent Document 1 can be suitably used. EXAMPLES

[0127] The present invention will be described in detail below with reference to examples and comparative examples. Unless otherwise specified, the preparation and evaluation of samples were carried out at room temperature in the atmosphere.

[0128] <Preparation of hard coat layer forming composition> A photopolymerization initiator "Omnirad127" (manufactured by IGM Resins BV) was added to an ultraviolet-curable resin composition ESS-620 (manufactured by DIC, urethane acrylate resin, solvent (ethyl acetate), solid content concentration 79% by mass) so as to be 3% by mass relative to the total amount of the composition for forming a hard coat layer. Further, ethyl acetate was added so as to be 31% by mass of solid content, thereby preparing a composition for forming a hard coat layer.

[0129] <Preparation of Composition for Forming High Refractive Index Layer> A composition for forming a high refractive index layer was prepared by adding methyl ethyl ketone to an ultraviolet-curable resin composition TYZ65-01 (manufactured by Toyochem, acrylic resin, containing zirconium oxide (average particle size 80 nm), photopolymerization initiator (the above-mentioned "Omnirad127"), solvent (cyclohexanone, methyl isobutyl ketone, propylene glycol monomethyl ether), solids concentration 35% by mass) so that the solids concentration was 8% by mass.

[0130] <Preparation of alumina particles surface-treated with a silane coupling agent having a reactive group> 25 g of untreated alumina particles (average particle diameter 160 nm), 2.5 g of a silane coupling agent (KBM-5103, manufactured by Shin-Etsu Chemical Co., Ltd., 3-acryloxypropyltrimethoxysilane), and 72.5 g of propylene glycol monomethyl ether were added to a 500 ml stainless steel pot, and the mixture was mixed and dispersed at 4,000 rpm for 30 minutes using a homomixer (Homomixer MARKII 2.5 type, manufactured by Primix Corporation), to obtain alumina particle dispersion 1 that was surface-treated with a silane coupling agent having an acryloyl group as a reactive group.

[0131] <Preparation of composition for forming low refractive index layer> A binder resin, hollow silica particles, alumina particles, fluorine-containing (meth)acrylate (only Example 2 and Comparative Example 2), and a photopolymerization initiator were mixed to obtain the composition shown in Table 1 (mass % of the total solid content), and the solid content concentration was adjusted to the concentration shown in Table 1 using a solvent (MEK / PGM=1 / 3), thereby preparing a composition for forming a low refractive index layer.

[0132] The materials used for the composition for forming the low refractive index layer are as follows. Binder resin: Toagosei's "Aronix MT-3041", multifunctional acrylate, solid content 100% by mass Hollow silica particles: JGC Catalysts and Chemicals "Surulia 4320", average particle size 60 nm, solvent: MIBK, solid content 20% by mass Alumina particles 1: the above-mentioned alumina particle dispersion 1 Alumina particles 2: Toyochem alumina sol "Lioduras KT-110AL", 25% by mass of alumina particles (average particle size: 110 nm, no surface treatment), 15% by mass of photosensitive monomer and resin, solvent (MEK, cyclohexanone, aliphatic solvent) Fluorine-containing (meth)acrylate: Shin-Etsu Chemical Co., Ltd. "KY-1216", perfluoropolyether group-containing (meth)acrylate, methyl ethyl ketone, solid content concentration 20% by mass Photopolymerization initiator: "Omnirad127"

[0133] <Preparation of Antifouling Layer-Forming Composition> A fluorine-containing compound (the above-mentioned "KY-1216") and a photopolymerization initiator (the above-mentioned "Omnirad127") were mixed to obtain the composition shown in Table 1 (mass % of the total solids), and the solids concentration was adjusted to the concentration shown in Table 1 using a solvent (MEK / PGM=1 / 3), thereby preparing a composition for forming an antifouling layer.

[0134] <Preparation of hard coat layer> For each of Examples 1 and 2 and Comparative Examples 1 to 3, the composition for forming a hard coat layer was applied to a substrate film (Toray's "Lumirror #50-U403", a polyethylene terephthalate film, thickness 50 μm) using a #12 wire bar, dried at 80°C for 60 seconds, and then irradiated with a high-pressure mercury lamp with a light intensity of 200 mJ / cm. 2 The coated film was irradiated with ultraviolet light to form a hard coat layer (film thickness: 4 μm).

[0135] <Preparation of high refractive index layer> For each of Examples 1 and 2 and Comparative Examples 1 to 3, a composition for forming a high refractive index layer was applied onto the surface of the hard coat layer, dried at 80°C for 60 seconds, and then irradiated with a light intensity of 200 mJ / cm using a high pressure mercury lamp in a nitrogen atmosphere. 2 The film was irradiated with ultraviolet light of 100 nm to form a high refractive index layer (thickness: 110 nm).

[0136] <Preparation of low refractive index layer> For each of Examples 1 and 2 and Comparative Examples 1 to 3, a composition for forming a low refractive index layer was applied onto the surface of the high refractive index layer using a #3 wire bar, and then dried at 100°C for 60 seconds. After that, the composition was irradiated with a high pressure mercury lamp at a light intensity of 200 mJ / cm under a nitrogen atmosphere. 2 The low refractive index layer was formed by irradiating the film with ultraviolet light of 1000 ohms.

[0137] <Preparation of antifouling layer> In Example 1 and Comparative Example 1, the composition for forming an antifouling layer was applied onto the surface of the low refractive index layer using a #3 wire bar, and then dried at 100°C for 60 seconds. After that, the composition was irradiated with a light intensity of 200 mJ / cm using a high-pressure mercury lamp in a nitrogen atmosphere. 2An antifouling layer was formed by irradiating the film with ultraviolet light of 1000 nm in wavelength. The film thickness was as shown in Table 1. In Example 2 and Comparative Examples 2 to 3, no antifouling layer was formed. As described above, antireflection films according to Examples 1 and 2 and Comparative Examples 1 to 3 were produced.

[0138] <Evaluation method> (Thickness and refractive index of each layer) The thickness and refractive index of each of the hard coat layer, high refractive index layer, low refractive index layer, and antifouling layer were evaluated for each sample. At this time, each time each layer was formed, the reflection spectrum in the wavelength range of 380 to 780 nm obtained using a microspectrophotometer (Otsuka Electronics' "OPTM-F1") and the theoretical spectrum derived based on the Fresnel equation were curve-fitted by the least squares method to calculate the thickness and refractive index of each layer at a wavelength of 589.3 nm.

[0139] (Luminous reflectance) The back surface of the anti-reflection film (the surface opposite to the low refractive index layer) was roughened with #400 sandpaper and painted with black paint, and the 5° regular reflectance of the surface of the anti-reflection film at wavelengths of 380 nm to 780 nm was measured using an ultraviolet-visible-near infrared spectrophotometer (Shimadzu Corporation's "UV-3600"), and the luminous reflectance was calculated by multiplying this measurement value by the relative luminous efficiency value. If the luminous reflectance is 2.0% or less, the anti-reflection properties can be considered sufficient.

[0140] (water contact angle) The water contact angle was measured for the surface of the anti-reflection film thus produced. For the measurement, a contact angle meter (DropMaster DMo-502, manufactured by Kyowa Interface Science Co., Ltd.) was used, and 4 μL of pure water was dropped onto the surface of the sample (the surface of the antifouling layer for Example 1 and Comparative Example 1, and the surface of the low refractive index layer for Example 2 and Comparative Examples 2 to 3) to measure the water contact angle. If the water contact angle is 100° or more, it can be considered to be sufficiently large from the viewpoint of antifouling properties.

[0141] (Abrasion durability) The abrasion resistance of each sample was evaluated by an eraser abrasion test using the water contact angle as an index. An eraser abrasion test was performed on each sample. In this case, a flat surface abrasion tester (Daiei Scientific Instruments & Associates, "DAS-400") was used, and an eraser for the eraser abrasion test (Minoan, cylindrical with a contact surface of φ6 mm in diameter) was placed on the surface of the anti-reflective film of each sample and reciprocated. The stroke length of the test stand was 50 mm, the reciprocation speed of the test stand was 30 reciprocations / min, and the applied load was 1.0 kg. The water contact angle was measured every 100 reciprocations up to 500 reciprocations, and every 500 reciprocations after 500 reciprocations, and the maximum number of reciprocations that maintained a water contact angle of 90° or more was used as the evaluation value. If the evaluation value was 2000 times or more, it can be considered that the sample had sufficient abrasion resistance. Furthermore, if the evaluation value was 4000 times or more, it can be considered that the sample had high abrasion resistance. The water contact angle was measured by dropping 4 μL of pure water onto the surface of the anti-reflective film using a contact angle meter (Kyowa Interface Science, DropMaster DMo-502).

[0142] (Solvent resistance) For each sample, an eraser abrasion test was carried out in the presence of ethanol, and the solvent resistance was evaluated using the water contact angle as an index. An eraser abrasion test was conducted for each sample. In this case, a flat surface abrasion tester (Daiei Scientific Instruments Manufacturing Co., Ltd. "DAS-400") was used, and an eraser for the eraser abrasion test (Minoan Co., Ltd., cylindrical with a contact surface of φ6 mm in diameter) was placed on the surface of the anti-reflective film of each sample and reciprocated 1500 times. The stroke length of the test table was 50 mm, the test table reciprocation speed was 30 reciprocations / min, and the applied load was 1.0 kg. At this time, 200 μL of ethanol was dropped using a micropipette on the part of each sample where the eraser contacted before the start of the test and after every 200 reciprocations. After 1500 reciprocations, the contact angle was measured, and if it decreased to less than 90°, the solvent resistance was evaluated as low (×). On the other hand, if the water contact angle was maintained at 90° or more, the solvent resistance was evaluated as high (◯). Furthermore, if a water contact angle of 90° or more was maintained and no wear marks (changes in reflectance properties at the location of friction) were observed, the solvent resistance was evaluated as particularly excellent (◎).

[0143] (Scratch resistance) A steel wool resistance test was carried out for each sample. In this case, a flat surface abrasion tester (Daiei Scientific Instruments Manufacturing Co., Ltd. "DAS-400") was used, and steel wool #0000 (manufactured by Japan Steel Wool Co., Ltd.) fixed to a flat surface abrader of 20 mm x 20 mm was placed on the surface of the anti-reflective film of each sample and reciprocated. The stroke length of the test table was 50 mm, the test table reciprocation speed was 60 reciprocations / min, and the applied load was 1.5 kg, and the anti-reflective film was reciprocated 100 times. After the test, anti-reflective films with scratches of 10 mm or more in length were evaluated as having low scratch resistance (x). In addition, anti-reflective films with scratches less than 10 mm in length but no scratches of 10 mm or more in length were evaluated as having high scratch resistance (◯). Scratches of this degree do not pose a practical problem. Furthermore, films without scratches were evaluated as having very high scratch resistance (◎).

[0144] <Evaluation Results> Table 1 shows the evaluation results for Examples 1-2 and Comparative Examples 1-3, together with the component compositions of the low refractive index layer and antifouling layer (unit: mass % of the total solid content of each layer) and the layer structure of the antireflection film.

[0145] [Table 1]

[0146] As shown in Table 1, in Examples 1 and 2, the water contact angle of the anti-reflection film surface is 100° or more, which indicates that the anti-reflection film has high antifouling properties. In addition, in all of Examples 1 and 2, high abrasion resistance with an evaluation value of 2000 times or more and high solvent resistance evaluated as "◎" or "○" are obtained. At the same time, high scratch resistance evaluated as "◎" is obtained. This is considered to be because the composition constituting the low refractive index layer contains alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound, in addition to the (meth)acrylate compound and hollow silica particles having a reactive group. In particular, in Example 1, a particularly high solvent resistance rated as "A" was obtained, corresponding to the presence of an antifouling layer made of a cured product of a composition containing a fluorinated (meth)acrylate on the surface of the low refractive index layer.

[0147] On the other hand, Comparative Examples 1 and 2 are different from Examples 1 and 2 in that the alumina particles contained in the low refractive index layer are not surface-treated with a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound. Correspondingly, the abrasion resistance and solvent resistance are low. The scratch resistance is also low compared to Examples 1 and 2. In Comparative Example 3, the water contact angle of the antireflection film surface was less than 100°, indicating that the antifouling properties of the antireflection film were low. The abrasion resistance, solvent resistance, and scratch resistance were also insufficient.

[0148] As described above, the anti-reflection film has a substrate film, a hard coat layer formed on the substrate film, and a low refractive index layer formed on the hard coat layer, or further has an anti-soiling layer formed on the low refractive index layer, and the low refractive index layer is made of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and the water contact angle of the anti-reflection film surface is 100° or more, so that the anti-reflection film has excellent anti-soiling properties and scratch resistance, as well as high wear resistance and solvent resistance. It can also withstand friction with cloth or fingers that have solvents such as alcohol attached to them.

[0149] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and various modifications can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0150] 10,20,30,40,50 Anti-reflective film 12 Base film 14 Hard coat layer 15 High refractive index layer 16 Low refractive index layer 18 Antifouling layer 22 Transparent adhesive layer 24 Release film 26 Adhesive layer 28 Protective Film

Claims

1. An anti-reflection film comprising a substrate film, a hard coat layer formed on a surface of the substrate film, and a low refractive index layer formed on the surface of the hard coat layer and having a refractive index lower than that of the hard coat layer, the low refractive index layer is composed of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and a fluorine-containing (meth)acrylate; The water contact angle of the surface of the anti-reflection film is 100° or more, a content of the alumina particles in the low refractive index layer is 0.1% by mass or more and 6.0% by mass or less with respect to 100% by mass of a solid content of the low refractive index layer; an antireflection film, wherein a difference (r−d) between an average particle diameter r of the alumina particles and a thickness d of the low refractive index layer in a thickness direction of a portion free of irregularities caused by the alumina particles is 10 nm or more and 100 nm or less.

2. An antireflection film comprising: a substrate film; a hard coat layer formed on a surface of the substrate film; a low refractive index layer formed on the surface of the hard coat layer and having a refractive index lower than that of the hard coat layer; and an antifouling layer formed on the surface of the low refractive index layer, the low refractive index layer is composed of a cured product of an ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles that have been surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, the antifouling layer is composed of a cured product of an ionizing radiation curable composition containing a fluorinated (meth)acrylate, The water contact angle of the surface of the anti-reflection film is 100° or more, a content of the alumina particles in the low refractive index layer is 0.1% by mass or more and 6.0% by mass or less with respect to 100% by mass of a solid content of the low refractive index layer; an antireflection film, wherein a difference (r−d) between an average particle diameter r of the alumina particles and a thickness d of the low refractive index layer in a thickness direction of a portion free of irregularities caused by the alumina particles is 10 nm or more and 100 nm or less.

3. The antireflection film according to claim 2 , wherein the content of the fluorinated (meth)acrylate in the antifouling layer is 90% by mass or more based on the total solid content of the antifouling layer.

4. The anti-reflection film according to claim 2 , wherein the low refractive index layer does not contain a fluorine-containing compound.

5. 5. The anti-reflection film according to claim 1, wherein the content of the silane coupling agent in the low refractive index layer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the alumina particles.

Citation Information

Patent Citations

  • Stain resistant self-cleaning powder paint

    CN107189646A

  • Anti-reflection article, polarizing plate, cover glass, image display device, and manufacturing method for Anti-reflection article

    JP2016167043A

  • Antireflection film and image display device

    JP2021144201A

  • Cured film and laminate, and method for producing the same

    JP2022025625A

  • Laminate for display device and display device

    JP2022165392A